Sensor element and method for producing a potentiometric sensor
By electrically connecting the substrate made of copper-based alloy in the potential sensor with conductive ground of the ion-selective enamel layer, combined with the copper oxide (I) transition zone, a full-function solid contact electrode is formed, which solves the complexity of manufacturing in the prior art. and the problem of insufficient stability achieves the effect of simplifying manufacturing and improving mechanical and thermal stability.
Patent Information
- Application Number
- CN202080058219.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-06
- Filing Date
- 2020-08-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-08-18
AI Technical Summary
The manufacturing process of existing potential sensors is complex, requiring multiple separate steps, and the stability and reproducibility of the sensor elements are insufficient, especially under mechanical and thermal loads.
Design of sensor elements with solid terminal leads, in which the substrate and the ion-selective enamel layer are electrically connected by conductive ground, the enamel layer is made of a copper-based alloy, and a fully functional solid contact electrode is formed in combination with the copper oxide (I) transition zone, simplifying Manufacturing process and improve mechanical and thermal stability.
It realizes a simple manufacturing process and high mechanical and thermal stability of sensor components, reduces the number of manufacturing steps, improves the reproducibility and stability of sensor components, and is suitable for a variety of application scenarios.
Smart Images

Figure CN114258487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sensor element of a potentiometric sensor, a potentiometric sensor and a method for producing a sensor element of a potentiometric sensor. Background Art
[0002] Potentiometric sensors are used in laboratory and process measurement technology in many areas of chemistry, biochemistry, pharmacy, biotechnology, food technology, water management and environmental measurement technology to analyze measurement media, in particular measurement liquids. Potentiometric sensors allow the detection of the activity of chemical substances, such as ion activity, and the associated measurement variables in liquids. The substance whose activity or concentration is to be measured is also called analyte. The measurement medium can be a measurement liquid, such as an aqueous solution, emulsion or suspension.
[0003] Potentiometric sensors typically include measuring electrodes and reference electrodes and a sensor circuit for detecting measured values and for signal processing. The measuring electrodes and reference electrodes can be combined in a measuring probe that can be immersed in a measuring liquid. The measuring probe can also include a sensor circuit or at least a portion of a sensor circuit. The measuring probe can be connected via a cable or wirelessly to communicate with a higher-level unit (e.g., a measuring transducer, an electronic operating device, a computer or a controller. The higher-level unit can be used to further process the measurement signal or measurement value detected by means of the measuring probe and to operate the measuring probe.
[0004] When in contact with the measurement medium, the measuring electrode forms a potential as a function of the activity of the analyte in the measurement medium, while the reference electrode provides a stable reference potential that is independent of the analyte concentration. The sensor circuit generates an analog or digital measurement signal, which represents the voltage (potential difference) between the measuring electrode and the reference electrode and therefore represents the activity of the analyte in the measurement medium. The measurement signal can be output from the sensor circuit to a higher-level unit, which further processes the measurement signal. Partial or complete further processing of the measurement signal in the sensor circuit in the measurement probe is also possible.
[0005] The reference electrode of a conventional potentiometric sensor is usually designed as a second type of electrode, such as a silver / silver chloride reference electrode, and is electrically connected to the sensor circuit in an electrically conductive manner. It can include a housing and a reference element, such as a silver wire coated with silver chloride, which is arranged in the housing and, in measuring operation, is in electrolytically conductive contact and / or ionically conductive contact with the measuring liquid via a reference electrolyte contained in the housing and an electrochemical bridge, such as a diaphragm.
[0006] The measuring electrode includes a sensor element that forms a potential, and the sensor element that forms a potential includes an ion selective membrane according to the type of potential sensor. An example of such a measuring electrode is an ion selective electrode (ISE). A conventional ion selective electrode has a housing that is enclosed by an ion selective membrane and accommodates an internal electrolyte in contact with the membrane. The ion selective electrode also includes a terminal lead in contact with the internal electrolyte. The terminal lead is electrically connected to the sensor circuit conductively. If the ion selective membrane used for measurement contacts the measuring medium, the membrane selectively interacts with the specific ion species contained in the measuring medium, i.e., interacts with the analyte. Changing the activity or concentration of the ions in the measuring medium causes a relative change in the equilibrium current voltage (galvanic voltage) between the measuring medium and the terminal lead in contact with the ion selective membrane via the internal electrolyte. A special case of such an ion selective electrode, i.e., an electrode that selectively detects the activity of hydronium ions in the measuring liquid, is a known pH glass electrode, which includes a glass membrane as a sensor element that forms a potential. The terms "ion-selective layer", "membrane" or "electrode" as used herein and hereinafter refer to an ion-sensitive layer, membrane or electrode, the potential of which is preferably predominantly influenced by the analyte, such as a specific ion type or pH value, wherein cross-sensitivity of the layer, membrane or electrode to other types of ions is not excluded, but is preferably low. The term "ion-selective glass" refers to a glass suitable for forming such an ion-selective layer, membrane or electrode.
[0007] Attempts have long been made to improve the design of measuring electrodes for potentiometric sensors with the goal of cost savings, simplified manufacturing, and greater robustness and longer service life. One approach that has been frequently adopted is to use solid terminal leads that do not need to contact the internal electrolyte of the ion-selective membrane.
[0008] An ion-selective electrode (also called a fixed contact electrode) with a solid terminal lead is described in WO 2018 / 069491 A1. The electrode comprises a measuring element having an ion-selective layer, which is in contact with the measuring medium during operation and is conductive to lithium ions. In addition, the measuring element has a conductive layer containing metallic lithium, a lithium (0) alloy or a conductive lithium compound. The measuring element also includes a solid electrolyte layer, which is arranged between the ion-selective layer and the conductive layer. The measuring element includes a series of other layers, which are used to protect the lithium-containing conductive layer from oxygen or moisture and are in contact with the ion-selective layer. Therefore, the manufacture of the sensor element requires a series of separate steps for constructing a layer stack and is correspondingly complex.
[0009] DE 10-2016-202083 A1 discloses a pH sensor having a terminal electrode with a metal reference electrode as a metal solid terminal lead and a pH-sensitive glass membrane made of lithium silicate glass applied to the reference electrode and further having a contact region made of a contact metal, such as copper, on the outer side of the metal reference electrode, wherein monovalent metal cations are formed. The glass membrane is doped with monovalent metal cations from the contact region of the reference electrode, so that a defined sensor potential is formed.
[0010] DE 1291139 B describes a glass electrode having a terminal electrode made of metal, preferably copper, which has an oxide scale on the surface with a glass layer fused to its upper surface.
[0011] DE 2220841 A describes a method for producing an ion-selective electrode in which a copper-plated palladium wire is coated with pH-sensitive glass, wherein the wire is heated at 850° C. in a flowing oxygen atmosphere and then the hot wire is immersed in crushed glass. The wire is then heated again in order to fuse glass particles thereto.
[0012] In Belford, RE, Owen, AE, Kelly, RG, Thick-Film Hybrid pH Sensors, Sensors and Actuators, Vol. 11, 1987, pp. 387-398, a method for producing a pH sensor in thick film technology is described, in which a pH glass film is applied to a printed metal conductor track. The conductor tracks are printed with the aid of a diluted Au / Pt paste. Between the conductor track and the glass film applied thereto, a metal oxide intermediate layer is produced by vapour deposition of copper or iron onto the printed conductor track and heating in air.
[0013] US 4,133,735 A describes a glass electrode with a solid terminal lead having a conductor with a surface layer made of an electrochemically active material such as copper. The surface layer has a first coating of a mixture of glass and a halogen of the active metal. The ion-sensitive glass coating is applied to the first coating by dipping the conductor into a melt of the ion-sensitive glass.
[0014] In the textbook H.Galster, "pH-Messung—Grundlagen, Methoden, Anwendungen, Some other methods of providing electrodes with solid terminal leads are described in "pH Measurement - Basic Principles, Methods, Applications, Apparatus", VCH Verlagsgesellschaft mbH, Weinheim, 1990, pages 135-136. One of these methods is formed by so-called enamel electrodes, which are usually built up from a plurality of layers of different composition, the uppermost layer being formed by a pH-selective enamel layer.
[0015] With regard to the term "enamel electrode" or "ion- or pH-selective enamel layer", the following should be noted. According to the definition / labeling standard from the RAL registration RAL-RG 529A2 of July 2007 by the RAL Deutsches Institut für Gütesicherung und Kennzeichnung eV (RAL German Institute for Quality Assurance and Certification, registered association), a glassy material produced by complete or partial melting of essentially oxidized raw materials is referred to as enamel. The inorganic preparation thus produced is applied together with additives to one or more layers of a workpiece made of metal or glass and fused at a temperature above 480° C. The basic components of the (ion-selective) enamel layer are one or more oxides such as silicon oxide, sodium oxide, potassium oxide, calcium oxide, magnesium oxide and aluminum oxide. In addition to the RAL definition, the definition of Adolf Dietzel and Hans Kyri is also common, according to which enamel is a preferably vitreous solidifying composition produced by melting or sintering using an inorganic, mainly oxidic composition, which composition is partially fused or has been fused to one or more layers of a workpiece of metal or glass using aggregates.
[0016] Therefore, within the types of these definitions, an ion-selective glass, such as a pH glass, applied to a metal substrate using the methods used in the RAL definitions or by fusing onto or to a substrate is referred to hereinafter as an ion-selective enamel layer or, in the case of an enamel layer specifically selective for hydronium ions, as a pH enamel layer, and the corresponding electrode is referred to as an enameled electrode.
[0017] Enamel electrodes are characterized by high mechanical stability and can be designed hygienically by providing an enamel coating covering all parts of the probe that come into contact with the process. They can therefore be used particularly advantageously in processes in the food industry and in chemical processes that require frequent purification.
[0018] Two examples of enameled electrodes are provided in the above-mentioned textbook of H. Galster. In the first example, an insulating enamel layer is arranged on an iron substrate, a silver layer is arranged on the insulating enamel layer, and a pH selective enamel layer is arranged on the silver layer. In this example, the silver layer serves as an electrical terminal lead. In the second example, a Pt / Pd layer is applied to a ceramic substrate of forsterite, an adhesive oxide layer of CuO / FeO is applied thereto, and a pH selective enamel layer of MacInnes glass is applied thereto. The individual layers are applied by means of thick film technology. The final ion selective layer is applied according to a screen printing process. For this purpose, a paste of ground MacInnes glass with a suitable binder is used, which is subsequently baked at 850° C.
[0019] The production of many sensor elements known from the prior art for potentiometric sensors is relatively complex and requires several or even multiple individual production steps. A reproducible and stable quality of the sensor elements produced in this way is also desirable. Summary of the invention
[0020] It is an object of the present invention to provide an improved sensor element for a potentiometric sensor which has solid terminal leads and is easy to manufacture. It is a further object of the present invention to provide a simple manufacturing method for such a sensor element.
[0021] A sensor element for a potentiometric sensor according to the present invention comprises:
[0022] substrate, and
[0023] an ion-selective enamel layer disposed on a substrate,
[0024] wherein the substrate has at least one region which is electrically conductively connected to the ion-selective enamel layer,
[0025] And wherein the region of the substrate which is electrically conductively connected to the ion-selective enamel layer (7) is made of a copper-based alloy having a mass fraction of at least 60% copper.
[0026] Since the enamel layer as sensor layer and the substrate region electrically conductively connected thereto already form a fully functional solid contact electrode, the sensor element has a very simple structure. The production of the sensor element is therefore also very simple compared to the solid contact electrodes known from the prior art and requires only a few method steps. The ion-selective enamel layer can be a pH enamel layer.
[0027] It has been found that the sensor element according to the invention is also surprisingly robust to mechanical and thermal loads. According to technical knowledge, a basic requirement for the mechanical stability of solid contact electrodes exposed to mechanical or thermal loads is that the thermal expansion coefficients of the materials involved are as identical as possible but at least differ by no more than 10%. The thermal expansion coefficients of known ion-selective glasses - for example pH glasses such as Macinnes glass, Corning 015 glass or the glass known, for example, from US Pat. No. 3,458,422 - are 10·10 -6 K -1 For example, the expansion coefficient of Corning 015 glass is 11·10 -6 K -1 , or the expansion coefficients of the glasses known from US Pat. No. 3,458,422 are 9.3 and 10.4·10 -6 K -1 On the other hand, copper has a 16.5·10 - 6 K -1 of thermal expansion coefficients. It has been found that the high ductility of copper, compared to, for example, typical steel, still enables very stable connection to ion-selective glass and conventional enamels for steel, even under thermal or mechanical loads. Here, the compressive stresses in the enamel layer in the cooled state remain high only in order to counteract flaking and cracking. Therefore, a sensor element for a potentiometric sensor can also have a substrate and an ion-selective enamel layer arranged on the substrate, wherein the substrate has at least one region that is electrically conductively connected to the ion-selective enamel layer, and wherein the region of the substrate that is electrically conductively connected to the ion-selective enamel layer is made of copper. Such a sensor element can be produced in a very similar manner to the sensor element here, which has at least one region that is electrically conductively connected to the ion-selective enamel layer, which region is formed by a copper-based alloy, and can be designed completely similarly, as described below for this sensor element. Copper-based alloys which contain other components in addition to copper, such as zinc or tin, are less ductile than pure copper and impart a higher mechanical stability to the sensor element with respect to mechanical loads, whereas in a similar manner copper-based alloys with a copper content of at least 60% by mass also prove to be sufficiently ductile to keep the compressive stresses acting on the enamel layer in the cooled state to a minimum, as in the case of a pure copper substrate.
[0028] The ion-selective enamel layer applied to the substrate region consisting of a copper-based alloy may have a thickness of less than 500 μm, preferably less than 300 μm or even less than 200 μm or even only less than 100 μm.
[0029] Suitable copper-based alloys are formed or produced with a defined copper component as main component with a mass fraction of at least 60% and other alloying components, respectively. The copper-based alloy may advantageously include zinc or tin as additional alloying components. Suitable copper-based alloys are, for example, red brass alloys used in the jewelry industry or in special device engineering, such as, for example, CuZn5 or CuZn10.
[0030] Advantageously, the region of the substrate made of a copper-based alloy which is electrically conductively connected to the enamel layer is in contact with the enamel layer via a transition zone comprising copper(I) oxide. This transition zone can be formed at least partially during the enameling, i.e. during the application of the enamel layer, due to corrosion, dissolution and transport processes. The copper from the substrate region covered by the formed enamel layer is oxidized to monovalent copper (also referred to as Cu(I) or copper(I)), which occurs in the copper-based alloy of the substrate in the region close to the surface and in the glass forming the enamel layer and acts as a very good adhesive via chemical bonding between the substrate region consisting of the copper-based alloy and the glass of the enamel layer.
[0031] In one possible embodiment, the transition zone can be an oxide layer comprising copper (I) or copper (I) oxide, the thickness of which is less than 5 μm, preferably less than 2 μm, more preferably less than 1 μm. The minimum thickness of this layer can be 0.05 μm or less. In an advantageous embodiment, the layer comprising copper (I) oxide is produced by a method step before enameling, which method step involves conditioning the substrate surface, such as a heat treatment or plasma treatment. In addition to copper (I) oxide, the layer comprising copper (I) oxide may also contain a portion of copper (II) oxide and oxides of other alloy components.
[0032] In one possible embodiment, the substrate may be a body formed of a copper-based alloy having a mass fraction of at least 80% copper. Alternatively, the substrate may be formed of at least one layer arranged on a substrate, in particular a metal or ceramic substrate, wherein at least one layer consists of a copper-based alloy. The layer may, for example, be formed as a small plate placed on the substrate and materially bonded thereto, or as a foil of a copper-based alloy placed on the substrate and materially bonded thereto.
[0033] The copper-based alloy may be, for example, Cu1-xSnx or Cu1-xZnx, where in each case x≤0.1. As further described above, these alloys with a mass fraction of, for example, greater than 90% copper have the advantage of a higher mechanical stability while still having sufficient ductility.
[0034] The ion-selective enamel layer can be formed by an ion-selective glass, in particular a pH membrane glass. Such an ion-selective glass can be formed by at least the following components: silicon oxide (SiO2), at least one alkali metal oxide (RO, where R=Li, Na, K, Rb or Cs) and at least one alkaline earth metal oxide (RO, where R=Mg, Ca, Sr, Ba). Optionally, the components forming the ion-selective glass can include a plurality of alkali metal oxides and / or a plurality of alkaline earth metal oxides. Optionally, the ion-selective glass can contain other additives, such as boron oxide (B2O3). If the sensor element is intended for potentiometric measurement of pH, sodium and / or lithium can be contained. Lithium-containing glass shows low or negligible cross-sensitivity to sodium ions in the measuring medium, while sodium-containing pH glass is generally easier to apply to the substrate by top enamel. For example, a glass containing lithium and not containing sodium or, alternatively, a glass containing sodium and not containing lithium is suitable as a pH glass.
[0035] The ion-selective enamel layer can be designed as a single-layer or multi-layer coating. The multi-layer application of the coating reduces the risk that the enamel layer is not completely sealed and thus reduces the danger of the measured medium reaching the substrate surface during the measuring operation of the sensor element.
[0036] The single-layer or multi-layer coating can be applied to a substrate region consisting of a copper-based alloy or to a layer comprising copper(I) oxide arranged on the surface of a region consisting of a copper-based alloy.
[0037] In an advantageous embodiment, the sensor element comprises a preamplifier and / or an impedance converter which can be connected to a potentiometric sensor circuit. One input of the preamplifier can be connected to a region of the substrate which serves as a conductive potential terminal lead of the sensor element and is electrically conductively connected to the ion-selective enamel layer, and a second input can be at the housing potential or at a virtual ground of the sensor circuit as a reference potential. For example, if the sensor element is a component of a potentiometric sensor, in which it serves as a measuring electrode and also has a reference electrode and a sensor circuit, the component being configured to detect a voltage between the measuring electrode and the reference electrode and to generate a measurement signal based on the voltage, then the preamplifier or the impedance converter can be used to increase the signal-to-noise ratio of the measurement signal. This is particularly advantageous if the ion-selective layer has a high impedance.
[0038] The preamplifier can be arranged in the cavity in the already mentioned base body, or in a housing at least partially surrounding the sensor element, or in a sheath of electrically insulating material surrounding the unit comprising at least the enamel layer and the substrate.
[0039] The invention also comprises a potentiometric sensor having at least one sensor element according to one of the above-described embodiments,
[0040] reference electrode, and
[0041] A sensor circuit is conductively connected to the sensor element and the reference electrode, wherein the sensor circuit is configured to detect a potential difference between the sensor element and the reference electrode.
[0042] The method according to the invention for producing a sensor element of a potentiometric sensor comprises applying an ion-selective enamel layer, in particular a pH-selective enamel layer, directly to a region of a substrate which consists at least of a copper-based alloy having a mass fraction of at least 60% copper. The method according to the invention can be used to produce the above-mentioned sensor element.
[0043] In the method, a fully functional sensor element suitable for measuring ion concentrations or pH values can be produced in one enameling step. In the sense of the definition given at the outset, the enameling step can include applying an enamel preparation followed by a heat treatment to form an enamel coating on a substrate, or melting or fusing the glass forming the enamel layer onto regions of the substrate. The method here and hereinafter can thus be used in a very simple manner to produce sensor elements with solid terminal leads for potentiometric sensors.
[0044] When the enamel layer is applied, a transition zone comprising copper(I) oxide or copper(I) is produced at the interface between the substrate area and the formed enamel layer, via which the substrate area is in conductive contact with the enamel layer. The transition zone can be electronically and / or ionically conductive. The transition zone can be formed in a temperature range between 400 and 1085° C.
[0045] In a first embodiment, applying the ion-selective enamel layer to the substrate region may comprise the following steps:
[0046] applying an enamel article of ion-selective glass, especially PH glass, to a substrate area; and
[0047] The enamel article applied to the substrate is heat treated to form an ion-selective enamel layer.
[0048] The heat treatment of the enameled article is performed at least intermittently at a temperature between 400°C and 1085°C.
[0049] The enamel product can be manufactured as a powder comprising at least glass particles from ion-selective glass, especially PH glass, or as a liquid or paste product comprising at least glass particles from ion-selective glass, especially PH glass. It may contain other additives.
[0050] In an advantageous embodiment of the method, the formation of more highly oxidized copper (II) oxide CuO is blocked. The CuO formed on the substrate surface is wetted more poorly by the ion-selective glass and may lead to defects in the glass coating. Therefore, it is advantageous to adjust the temperature sequence of the heat treatment in a way that offsets the formation of CuO, for example, by exposing the substrate to which the enamel article is applied to high temperatures in the shortest possible time period. Advantageously, the enamel article may contain substances that form low melting point salts such as boric acid hydrates, nitrates or carbonates. These may form a protective film on the substrate during heating.
[0051] In a second embodiment, applying the ion-selective enamel layer to the substrate region may include:
[0052] A glass body made of ion-selective glass is applied to a region of the substrate and the glass body is fused to the substrate to form the ion-selective enamel layer. The fusion can be carried out, for example, by means of a heat treatment in a furnace or by heating with a gas flame or with a laser. In an advantageous method embodiment, the temperature occurring in the process is at least temporarily in the range between 400° C. and 1085° C.
[0053] The advantage of this process variant is that during the melting or fusion process of the glass body, CuO formation does not occur or only to a small extent at the substrate surface and the formation of the desired Cu2O is promoted.
[0054] In a third embodiment, applying the ion selective enamel layer to the substrate region may include:
[0055] A melt of the ion-selective glass is applied to the region of the substrate and the melt is solidified to form the ion-selective enamel layer.Solidification of the melt can optionally be achieved by defined cooling, such as actively controlled or regulated cooling.
[0056] In all method embodiments described herein, the ion selective enamel layer is applied to the substrate area and can be completed in the air in a classical manner. Alternatively, in all method designs described herein, the application of the enamel layer can be carried out completely or partially in an oxygen-free or low oxygen atmosphere or under an inert gas. For example, nitrogen or an inert gas such as argon is suitable as a protective gas or an inert gas. By controlling the oxygen content present in the atmosphere during the application of the ion selective enamel layer, the corresponding ratio of the Cu (I) oxide present in the transition zone can be influenced and / or specifically regulated, especially the ratio relative to the Cu (II) oxide also present in the transition zone. The upper enamel under a protective gas or in an oxygen-deficient atmosphere counteracts the formation of CuO.
[0057] The ion-selective glass used in all method embodiments disclosed herein can be a pH glass or a sodium, potassium or lithium selective glass. If the sensor element is intended for potentiometric measurement of pH, lithium-containing and / or sodium-containing pH glasses are preferred. Lithium-containing glasses show low or negligible cross-sensitivity to sodium ions in the measured medium, while sodium-containing pH glasses are generally easier to apply to substrates by over-enamelling. The glass can be constructed as described above in conjunction with the description of various advantageous embodiments of the sensor element.
[0058] The ion-selective enamel layer can be formed, for example, by applying one or more layers successively and one after another on the substrate area to be electrically conductively connected to the enamel layer, so as to ensure that it completely covers the substrate. At least one base layer in the multilayer enamel layer applied directly on the substrate can be formed by an electronically conductive and / or ion-conductive enamel, the composition of which is different from the ion-selective glass on which the one or more layers are formed. The at least one base layer provides an electrically conductive contact between the substrate and the cover layer of the ion-selective glass. The at least one base layer can also improve the adhesion of the ion-selective enamel layer to the substrate.
[0059] The substrate may be a body formed of a copper-based alloy having a mass fraction of at least 80% copper. Alternatively, the substrate may be formed of at least one layer arranged on a substrate, in particular a metal or ceramic substrate, the at least one layer consisting of a copper-based alloy.
[0060] In addition to copper, the copper-based alloy may also contain, for example, tin or zinc as a further component. The copper-based alloy may be, for example, Cu1-xSnx or Cu1-xZnx, where x≤0.1 in each case. As further described above, these alloys have the advantage of higher mechanical stability while still having sufficient ductility.
[0061] As a further step, the method may comprise conditioning at least a substrate region consisting of a copper-based alloy to produce a monovalent oxide layer (Cu(I)) with copper on the surface of the substrate region. The conditioning may be carried out during or before the application of the ion-selective enamel layer. The conditioning may comprise, for example, passivation, in particular by thermal pretreatment or plasma pretreatment. Due to the conditions prevailing during the conditioning, such as the temperature and / or oxygen content of the environment, the proportion of monovalent copper in the oxide layer produced by the conditioning may be adjusted in a controlled or targeted manner. The conditioning may, for example, comprise passivation, for example by thermal pretreatment or plasma pretreatment. The conditioning may comprise passivation by thermal treatment at a temperature between 300° C. and 600° C., advantageously between 400° C. and 500° C. The passivation may be carried out in an oxygen-deficient atmosphere, for example in an atmosphere having essentially one or more inert gases, such as nitrogen, and oxygen, at a partial pressure of 0.001 and 10 hPa. This low oxygen content is sufficient to produce a thin copper(I)-containing oxide layer on the substrate surface, for example with a thickness between 0.05 and 2 μm.
[0062] It has been found that such a pretreatment and the presence of a copper(I) oxide-containing layer produced on the substrate surface leads to the formation of a homogeneous and low-defect enamel layer during the subsequent enameling. This is accompanied by an improved stability with respect to mechanical loads and an improved sensor behavior, in particular an increase in the sensor gradient of the sensor element or a potentiometric sensor comprising the sensor element, compared to the enameled untreated copper-based alloy substrate. Advantageously, the copper(I) oxide-containing oxide layer formed during conditioning or passivation has a thickness of less than 5 μm, preferably 2 μm. Obviously, substantially thicker oxide layers are less stable and can partially detach.
[0063] In addition to copper (I), the layer thus produced can also contain preferably small proportions of copper (II), as well as other alloying components in oxidized form. It is advantageous for producing sensor elements with reproducible mechanical and / or sensory qualities that, by controlling the oxygen content, a controllable, in particular defined, copper (I) fraction can be produced in the oxide layer with copper (I). As a result of the conditions selected during the conditioning, an oxide layer which is defined, in particular with respect to its Cu (I) fraction, can be produced on the substrate in a reproducible manner and therefore also has defined, in particular reproducible, wetting properties during the enameling. The conditioning of these properties of the substrate surface is in particular also independent of the composition of the enamel to be applied or the glass to be fused. This advantage is achieved, for example, by carrying out the conditioning in a separate step upstream of the enameling.
[0064] Conditioning of the substrate area may include a thermal pretreatment, for example in an oven, by means of a flame or by means of a laser. Alternatively, conditioning of the substrate may include a plasma treatment of the surface, for example in an oxygen plasma. Conditioning may also be performed by applying an oxide layer by means of a coating process from the gas phase, for example by (reactive) sputtering, CVD (chemical vapor deposition) or ALD (atomic layer deposition).
[0065] After application of the ion-selective enamel layer, the monovalent copper-containing oxide layer formed during the conditioning can at least partially remain as a component of the transition zone, but can also be completely dissolved in the transition zone during application of the enamel layer.
[0066] The application of at least the ion-selective enamel layer to the substrate region described further above can then be carried out in a single enameling step or in several enameling steps. In this way, the enamel layer is applied to the oxide layer having Cu(I) and previously produced by conditioning. Advantageously, the enamel layer is applied in a single-stage enameling step in which a single ion-selective enamel layer is produced. However, the application of the enamel layer in several layers is not excluded. If the enamel layer is applied in a single-stage enameling step, this enables the production of particularly thin ion-selective enamel layers. The defined oxide layer in the substrate region to be enameled - which layer is produced by conditioning and has Cu(I) - indicates a defined wetting behavior during enameling, so that enamel defects are minimized, and the enamel layer can be applied in one layer and / or relatively thinly, preferably with a thickness of less than 500 μm. Advantageously, the enamel layer can be applied with a thickness of less than 300 μm, less than 200 μm or even less than 100 μm, wherein the enamel layer covers the underlying area of the substrate as a substantially closed layer, in particular in a liquid-tight manner, despite this minimum thickness.
[0067] The method can further comprise the step of sheathing the unit comprising at least the enamel layer and the substrate with an electrically insulating material, such that the sheath formed in this way leaves open only the surface of the enamel layer facing away from the substrate in the region of the sensor element intended to come into contact with the measured medium. An electrical conductor contacting the substrate can pass through the sheath in order to contact the substrate from outside the sheath.
[0068] The method steps of cladding a unit comprising an enamel layer and a substrate may include:
[0069] applying a powder comprising glass particles or a suspension or paste comprising glass particles to the cell; and
[0070] The applied powder or suspension or paste is heat treated to form the glass layer constituting the sheath.
[0071] Alternatively, the method step of encapsulation may also include applying a glass melt to the unit and cooling the glass melt or encapsulating the unit with plastic or ceramic.
[0072] The present invention also includes a sensor element manufactured according to the previously described method, for example in one of the variants thereof described herein. The resulting sensor element can have the structural and functional characteristics of the above-described sensor element. In principle, in the above-described method or in one of the method variants described herein, an ion-selective enamel layer can also be applied to an area of a substrate consisting of copper in order to produce a sensor element for a potentiometric sensor. The sensor element manufactured according to the above-described method can be used as a measuring electrode in a potentiometric sensor for measuring the ion concentration or pH in a measuring liquid. The potentiometric sensor can also have a potential-stable reference electrode and a measuring circuit, wherein the measuring circuit generates a measurement signal that depends on the voltage between the reference electrode and the measuring electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] In the following, the invention is explained in further detail based on the exemplary embodiments shown in the drawings.
[0074] The following is shown:
[0075] Figure 1 is a schematic longitudinal sectional view of a sensor element for a potential sensor according to a first exemplary embodiment;
[0076] Figure 2 is a schematic longitudinal sectional view of a potentiometric sensor having a sensor element according to a first exemplary embodiment; and
[0077] Figure 3 is a schematic longitudinal sectional view of a sensor element for a potential sensor according to a second exemplary embodiment. DETAILED DESCRIPTION
[0078] Figure 1 A sensor element 1 for a potentiometric sensor according to a first exemplary embodiment is schematically shown in longitudinal section. The sensor element 1 has a substrate 3 in the form of a rod made of a copper-based alloy having a mass fraction of at least 60% and an ion-selective enamel layer 7 serving as a sensor layer, which is arranged directly on the substrate 3 in a front region intended to be in contact with a liquid, in particular an aqueous, measurement medium 5. In the present example, the enamel layer 7 consists of a sodium or pH-selective glass, such as Macinnes glass, Corning 015 glass or any glass known from US Pat. No. 3,458,422. The glasses mentioned in US Pat. No. 3,458,422 contain a portion of Li2O and no Na2O, thereby reducing the cross-sensitivity of the pH measurement with the sensor layer of one of these glasses. Alternatively, however, a pH glass containing sodium can also be used.
[0079] The enamel layer 7 can be applied to the substrate 3 in one or more layers arranged one above the other. An electrically conductive, ie electronically and / or ionically conductive, transition region 9 is formed between the substrate 3 and the enamel layer 7. Figure 1-3 The thickness and thickness ratio of the transition zone 9 and the enamel layer 7 are shown greatly exaggerated in FIG. When the enamel layer 7 is applied, the transition zone 9 is formed at least in part by enamelling due to redox reactions (e.g., corrosion) and transport processes (e.g., diffusion) at the temperature occurring in the process. In the transition zone, copper (I) oxide is present in the area of the substrate 3 covered by the enamel layer 7, as well as in the glass forming the enamel layer 7. Therefore, the chemical bonding of Cu2O present in the transition zone 9, the enamel layer 7 and the substrate 3 leads to good adhesion of the enamel layer 7 to the substrate 3. Even after enameling, i.e., after forming and cooling the enamel layer 7, the transition zone 9 remains stable. It produces a good conductive electrical connection between the enamel layer 7 serving as an ion-selective sensor layer and the substrate 3 serving as a potential terminal lead.
[0080] The substrate 3 and the transition region 9 serve as solid terminal leads for the electrode potential formed on the ion-selective enamel layer 7 in contact with the measured medium 5. On the back side, i.e. on the side facing away from the measured medium 5, the substrate 3 has a contact point 10 at which an electrical conductor 11, for example a metal wire or a conductor path, is in electrical contact with the substrate 3. This conductor 11 can be connected to the sensor circuit of a potentiometric sensor.
[0081] Furthermore, the sensor element 1 has a sheath 12 which, in the present example, is formed by an insulating enamel layer. Alternatively, the sheath can be formed by a polymer instead of a glass enamel layer. It tightly surrounds the body of the substrate 3 and the edge regions of the layers 7 and 9 so that no liquid, in particular no measured medium 5, reaches the substrate 3.
[0082] The sheath 12 can be produced using known methods in connection with enameled metal substrates. Suitable materials for the sheath 12 and suitable methods for applying the sheath 12 to the unit formed by the substrate 3 and the ion-selective enamel layer 7 with the transition zone 9 arranged therebetween can be taken, for example, from EP 1 231 189 A1. The sheath 12 can be produced by applying particles of a glass composition to the substrate 3 and the enamel layer 7 and subsequently heat treating.
[0083] Figure 2 A schematic longitudinal section through a potentiometric sensor 100 for measuring the activity or concentration of analyte ions or a measured variable dependent thereon, such as the pH value, is shown with the sensor element 1 as measuring electrode and the reference electrode 13 .
[0084] The sensor element 1 corresponds substantially in structure to Figure 1The sensor element 1 shown in FIG. It has an ion-selective enamel layer 7 as a sensor layer, which is applied to a cylinder made of a copper-based alloy serving as a substrate 3, wherein a transition zone 9 comprising copper (I) oxide is formed between the enamel layer 7 and the substrate. In addition, the sensor element 1 comprises a sheath 12, which surrounds the substrate 3 and leaves open only the surface of the enamel layer 7 intended to be in contact with the measured medium, the sheath being made of an insulating enamel or polymer, which insulates the substrate 3 and the edge region or transition zone 9 of the enamel layer 7 from the liquid medium.
[0085] The reference electrode 13 can be designed as a conventional electrode of the second type, for example as a silver / silver chloride electrode. In the example shown here, the reference electrode 13 includes a tubular housing 19, which surrounds a section of the sheath 12 of the substrate 3 and is closed by an annular diaphragm 21 at its front end facing the measured medium. The diaphragm 21 can be formed, for example, of a plastic such as PTFE (or a porous ceramic such as ZrO2 ceramic. The annular chamber formed between the sheath 12 and the housing 19 contains a reference electrolyte, such as a KCl solution, in which a reference element 23, such as a silver electrode coated with silver chloride, is impregnated. Instead of the diaphragm 21, the reference electrode 13 can also have other bridges that establish ion-conducting contact and / or electrolyte contact between the reference electrolyte and the measured medium. The annular chamber containing the reference electrolyte is closed on its back side, for example by casting or adhesive bonding.
[0086] The substrate 3 is connected to the sensor circuit 25 via the first wire 11 and thus forms the measuring electrode of the potentiometric sensor 100. The sensor circuit 25 is housed in an electronic housing 27 connected to the reference electrode and the measuring electrode of the sensor 100. The reference element 23 comes out of the annular chamber by casting or bonding and is also connected to the sensor circuit 25. The sensor circuit 25 is configured to detect the voltage generated by contacting the diaphragm 21 and the ion selective enamel layer 7 with the measuring medium between the measuring electrode 1 and the reference electrode 13. The voltage is a function of the activity of the analyte ions present on the ion selective enamel layer 7. The sensor circuit 25 can be configured to generate a measurement signal representing the detected voltage and output it to, for example, a measuring transducer, which is connected to the sensor circuit 25 and processes the measurement signal, and determines therefrom a measured value of the ion concentration of the analyte ions using a predetermined calibration function, or if the potentiometric sensor 100 is designed as a pH sensor, a measured value of the pH value. Alternatively, the sensor circuit 25 can also be configured to determine a measured value and output it via the interface 29 to a measuring transducer or another operating or display device.
[0087] Figure 3Another exemplary embodiment of a sensor element 1 for a potentiometric sensor is schematically shown. The sensor element 1 has a base body 31 made of ceramic or glass ceramic, on which a substrate 3 formed of a metal alloy is arranged in the form of a layer. The layer can be formed by a foil of a copper foil or a copper-based alloy or a small plate bonded, adhered or otherwise fastened to the base body. The ceramic of the base body can be, for example, a zirconium oxide ceramic or an aluminum oxide ceramic.
[0088] An ion-selective enamel layer 7 serving as a sensor layer is applied to a substrate 3. A transition zone 9 containing copper (I) oxide is arranged between the enamel layer 7 and the substrate 3. Figure 1 The enameling of the substrate 3 and the simultaneous formation of the transition zone 9 are performed in the same manner as disclosed in the exemplary embodiment described in .
[0089] The transition region 9 is electrically conductive, for example ionically and / or electronically conductive, and together with the substrate 3 forms a solid terminal lead of the sensor element 1. At the contact point 10, the substrate 3 is contacted on the back side with an electrical conductor 11, which passes through the base body 31 and can connect the sensor element 1 to the sensor circuit of the potentiometric sensor. The unit formed by the base body 31, the substrate 3, the transition region 9 and the ion-selective enamel layer is embedded in a glass sheath 12, which leaves only the surface area of the ion-selective enamel layer 7 and insulates the interface between the substrate 3 and the base body 31 and between the substrate 3 and the upper cover layer from the measured medium.
[0090] Optionally, the sensor element can include a preamplifier and / or an impedance converter (not shown here) for increasing the signal-to-noise ratio of the measurement signal of the sensor element or of a potentiometric sensor having the sensor element. If the ion-selective enamel layer has a high impedance, it is particularly advantageous to integrate a preamplifier in the signal path close to the ion-selective enamel layer.
[0091] A potentiometric sensor comprising a sensor element 1, shown here as a measuring electrode, can have a reference electrode which is also completely formed by a layer stack and whose potential terminal leads are designed as solid terminal leads. The two electrodes can be arranged on a common substrate, for example a circuit board or a non-conductive ceramic, and connected to the sensor circuit via wires, for example a conductor path extending on the substrate. In this way, very small potentiometric sensors can be realized.
[0092] To produce Figures 1 to 3 In the sensor element 1 shown in FIG. 1 , the enameling of the substrate 3 can be performed in the following manner:
[0093] In a first method variant, an enamel product, for example a powder formed of glass particles of an ion-selective glass or a suspension or paste containing glass particles of an ion-selective glass, can be applied to the surface of a substrate 3 and heated to a temperature between 800-850° C., depending on the composition of the ion-selective glass. The heat treatment forms the enamel layer 7, while at least partially forming the transition zone 9. This method has been shown to be very suitable for applying an enamel layer 7 containing lithium and / or sodium. Since the glass forming the enamel layer 7 wets CuO-containing surfaces significantly worse than Cu2O-containing or copper-containing surfaces, it is advantageous to suppress the formation of CuO on the substrate surface in this embodiment. For this purpose, the enamel product can advantageously contain components that form low-melting salts, such as boric acid hydrates, carbonates or nitrates. Advantageously, the heat treatment takes a few minutes, for example less than 15 minutes.
[0094] In a second method variant, a glass body of an ion-selective glass, for example a glass pane, can be placed and fused onto the substrate 3. Here, too, a temperature in the range of 400° C. to 1085° C. should be reached in order to ensure that, in addition to the resulting enamel layer, an ion-selective enamel layer 7 and a transition zone 9 containing Cu(I) are formed.
[0095] This method has proven to be particularly suitable for lithium-free, sodium-containing pH-selective glasses and sodium-selective glasses. Advantageously in this method, during the fusion of the glass body, no CuO formation at the surface of the substrate 3 is observed.
[0096] In other method variants, before enameling, the substrate 3 can be conditioned, for example passivated, so that a copper-containing oxide layer containing copper(I) oxide (i.e. monovalent) is produced on the substrate surface, which oxide layer can form part of the transition zone 9 after application of the enamel layer 7. Depending on the prevailing conditions during enameling, however, the oxide layer can also be at least partially or even completely dissolved in the transition zone 9 during application of the enamel layer.
[0097] An oxide layer with copper (I) can be produced by heat treating the surface of the substrate 3, for example, in a flame, by means of a laser or in an oven, in air or under an oxygen-poor or oxygen-free protective gas atmosphere. Similarly, an oxide layer can be produced by treatment in an oxygen plasma or by a coating method, such as sputtering or vapor deposition. The ratio of copper (I) and copper (II) present in the oxide layer can be controlled by adjusting the process conditions and the amount of oxygen provided. For example, the substrate can be heated to a temperature of 400 to 500° C. in an atmosphere of a protective gas with a low oxygen content, such as nitrogen. This can be carried out, for example, in a furnace chamber continuously purged with nitrogen, wherein the oxygen partial pressure is about 0.8 hPa. The heat treatment produces an oxide layer containing a high proportion of monovalent copper Cu (I). The layer has a thickness of less than 5 μm or even less than 1 μm. In addition to monovalent copper, the oxide layer can also contain oxides of Cu (II) and other alloy components. The Cu(I) fraction in the oxide layer can be controlled or selectively adjusted via the conditions prevailing during passivation (e.g., temperature program, gas atmosphere, especially its oxygen content). This allows, for example, to reproducibly adjust the substrate for subsequent enamelling to produce multiple sensor elements with similar properties.
[0098] The ion-selective glass layer can be applied to the passive surface of the substrate by enameling, for example by application of the enamel preparation further described above, also known as enamel glaze slurry, followed by heat treatment of the article to form the enamel layer, or by fusing glass plaques. The preferred layer thickness of the oxide layer after passivation is between 0.05 μm and 2 μm, preferably less than 1 μm. The substantially thicker oxide layer produced on a copper-based alloy with copper as the main component, for example an oxide layer with a thickness of more than 20 μm, can be separated from the metal substrate very easily as scale. In contrast, the layer with the layer thickness shown adheres firmly and also leads to good adhesion of the enamel layer after the subsequent application of the enamel layer. It can also be seen that the aforementioned passivation of the metal surface leads to uniform wetting of the metal or alloy surface during the enameling step, so that the formed enamel layer has significantly fewer enamel defects-such as cracks, irregularities or holes-than the enamel layer applied to the non-passivated substrate. Therefore, the enamel layer on the passivated substrate can be applied relatively thinly and still cover the substrate in a liquid-tight manner. This makes it possible to provide a sensor layer with a relatively low impedance for the sensor element. The ion-selective enamel layer of the conventional enamel electrode according to the prior art is usually thicker than the ion-selective membrane of the conventional glass electrode with liquid discharge to ensure that the enamel layer covers the potential discharge of the enamel electrode in a liquid-tight manner. Therefore, the ion-selective enamel layer of the conventional enamel electrode has a higher impedance than the glass membrane of the conventional glass electrode. In order to compensate for this, the surface of the ion-selective enamel layer is selected to be relatively large for the conventional enamel electrode used in the processing industry, so that the conventional enamel electrode requires significantly larger installation space than the conventional glass electrode with liquid discharge. In contrast, the ion-selective enamel layer of the sensor element produced according to the method described herein can have a thickness of less than 500 μm, or less than 300 or 200 μm, or even less than 100 μm. Therefore, the surface of the ion-selective enamel layer can also be kept small in order to provide a sensor element with a smaller required installation space.
[0099] As already mentioned in the introduction, the application of the ion-selective enamel layer can be carried out in a conventional manner by enameling in air or in an oxygen-free or low-oxygen protective atmosphere in order to influence the ratio of Cu(I) and Cu(II) present in each case in the transition zone produced here between the substrate and the formed glass layer.
Claims
1. A sensor element (1) for a potentiometric sensor (100), comprising: a substrate (3), and an ion-selective enamel layer (7) arranged on the substrate (3), The substrate (3) has at least one region which is electrically conductively connected to the ion-selective enamel layer (7). Characterized in that the region of the substrate which is electrically conductively connected to the ion-selective enamel layer (7) is made of a copper-based alloy having a mass fraction of at least 60% copper; wherein the transition region (9) has a layer comprising Cu2O, the thickness of the layer being less than 5 μm; and The region of the copper-based alloy electrically conductively connected to the ion-selective enamel layer (7) is in contact with the ion-selective enamel layer (7) via a transition region (9) comprising Cu2O.
2. The sensor element (1) according to claim 1, in, The thickness is less than 2 μm.
3. The sensor element (1) according to claim 2, in, The thickness is less than 1 μm.
4. The sensor element (1) according to any one of claims 1 to 3, in, The substrate is a body formed of a copper-based alloy having a mass fraction of at least 80% copper.
5. The sensor element (1) according to any one of claims 1 to 3, in, The substrate (3) is formed by at least one layer arranged on a base body (31), wherein the at least one layer consists of a copper-based alloy.
6. The sensor element (1) according to claim 5, in, The substrate (31) is a metal substrate or a ceramic substrate.
7. The sensor element (1) according to any one of claims 1 to 3, in, The copper-based alloy is Cu1-xSnx or Cu1-xZnx, wherein x≤0.
1.
8. The sensor element (1) according to any one of claims 1 to 3, in, The ion selective enamel layer (7) is formed of ion selective glass.
9. The sensor element (1) according to claim 8, in, The ion selective enamel layer (7) is formed of pH membrane glass.
10. The sensor element (1) according to any one of claims 1 to 3, in, The ion selective enamel layer (7) is configured as a single layer or a multilayer coating, which is applied to the region of the substrate formed of the copper-based alloy, or to a Cu2O layer arranged on the surface of the region composed of the copper-based alloy.
11. A potential sensor (100), comprising: at least one sensor element (1) according to any one of claims 1 to 10, a reference electrode (13), and A sensor circuit (25) is conductively connected to the sensor element (1) and the reference electrode (13), wherein the sensor circuit (25) is configured to detect a potential difference between the sensor element (1) and the reference electrode (13).
12. A method for manufacturing a sensor element (1) for a potentiometric sensor (100), comprising: applying an ion-selective enamel layer (7) directly to a region of the substrate (3) which consists at least of a copper-based alloy having a mass fraction of at least 60% copper, wherein, when the ion-selective enamel layer (7) is applied, a transition zone (9) comprising Cu2O is produced at the interface between the region of the substrate and the formed enamel layer, and the region of the substrate is in conductive contact with the enamel layer via the transition zone (9), and wherein the transition region comprises Cu2O having a thickness of less than 5 μm; Wherein, applying the ion-selective enamel layer (7) to the region of the substrate (3) comprises: applying an ion-selective glass enamel article to said area of said substrate; and The enamel article applied to the substrate is heat treated to form the ion-selective enamel layer.
13. The method according to claim 12, in, The ion-selective enamel layer is a pH-selective enamel layer.
14. The method according to claim 12, in, The ion-selective glass is PH glass.
15. The method according to claim 14, in, The heat treatment of the enameled article is performed at least intermittently at a temperature between 400°C and 1085°C.
16. The method according to any one of claims 12 to 15, in, The enamel product is produced as a powder comprising at least glass particles from the ion-selective glass, or as a liquid or paste product comprising at least glass particles from the ion-selective glass.
17. The method according to claim 16, in, The ion-selective glass is PH glass.
18. The method according to claim 12 or 13, in, Applying the ion-selective enamel layer (7) to the area of the substrate (3) comprises: A glass body made of ion-selective glass is applied to the region of the substrate (3), and the glass body is fused to the substrate to form the ion-selective enamel layer (7).
19. The method according to claim 12 or 13, in, Applying the ion-selective enamel layer (7) to the area of the substrate (3) comprises: A melt of an ion-selective glass is applied to the region of the substrate (3) and the melt is solidified by defined cooling to form the ion-selective enamel layer (7).
20. The method according to any one of claims 12 to 15, in, The substrate (3) is a body formed of a copper-based alloy having a mass fraction of at least 80% copper.
21. The method according to any one of claims 12 to 15, in, The substrate (3) is formed by at least one layer arranged on a base body (31), wherein the at least one layer consists of a copper-based alloy.
22. The method according to claim 21, in, The substrate (31) is a metal substrate or a ceramic substrate.
23. The method according to any one of claims 12 to 15, in, Prior to applying the ion-selective enamel layer (7), the substrate (3) is conditioned by a thermal pretreatment or a plasma pretreatment.
24. The method according to claim 23, in, Prior to applying the ion-selective enamel layer (7), the substrate (3) is passivated by thermal pretreatment or plasma pretreatment.
25. The method according to any one of claims 12 to 15, Further including: A unit comprising at least the ion-selective enamel layer (7) and the substrate (3) is sheathed with an electrically insulating material, so that the sheath (12) formed in this way leaves open only the surface of the ion-selective enamel layer (7) facing away from the substrate (3) in the region of the sensor element (1) intended to come into contact with the measured medium (5).
26. The method according to claim 25, in, An electrical conductor contacting the substrate (3) passes through the sheath (12) so as to contact the substrate (3) from the outside of the sheath (12).
Citation Information
Patent Citations
glass electrode
DE1291139B
Method of making an ion-selective electrode
DE2220841A1
Highly corrosion-resistant enamel composition free from heavy metals, method for its production, use and coated bodies
EP1231189A1
Peters
US104106A
Laminated glass electrode diaphragm
US3458422A